Coronary artery lesion risk and mediating mechanism in children with complete and incomplete Kawasaki disease. (25th February 2019) - Shi, Hongying; Qiu, Huixian; Jin, Zengyou; Li, Chen; Yang, Xinjun; Huang, Chenping; Wu, Rongzhou; Zhuang, Guihua; Chu, Maoping
Abstract : To compare the risk of coronary artery lesions (CAL) in children with complete and incomplete Kawasaki disease (KD) before and after immunoglobulin therapy and explore the mediation mechanisms underlying this association. All patients with KD admitted to the Wenzhou Medical University affiliated Yuying Children's Hospital were divided into complete and incomplete KD groups. The independent effect of KD type on the risk of CAL and the intermediate effect of admission time on the association between KD type and CAL were assessed. The incidence of CAL in children with incomplete KD was higher than that in children with complete KD (33.9% vs 23.0%, p<0.001), and was also higher before therapy (27.5% vs 14.8%). Among children without CAL before therapy, there was no statistical difference in the incidence of CAL after treatment between the two groups. Mediation analysis found that the mediating effect of admission time was 1.07 (95% C: 1.01 to 1.13), and the direct effect of KD type on CAL was 1.59 (95% CI 1.17 to 2.16); proportion mediated was 15.71%. In conclusion, the risk of CAL among patients with incomplete KD was higher than that for complete KD, especially before therapy. In patients without CAL before treatment, the risk of CAL after treatment was equivalent for the two groups. Delayed admission may be one of the important mediating mechanisms for the higher risk of CAL in incomplete KD children.